Assessment of the implementation of the Italian National action plan to combact antimicrobial resistance (PNCAR) 2017–2021 through SPiNCAR-1: results for the Piedmont Region, 2022 - Stefania Di Giacomo; Luca Bresciano; Lorenza Ferrara; Sabina Pederiva; Carla Maria Zotti; Fortunato “Paolo” D’Ancona; Costanza Vicentini; Collaborating Group (Antimicrobial Resistance and Infection Control)
Abstract Background The Italian National action plan to contrast antimicrobial resistance (PNCAR) was adopted in Italy with the aim of reducing antimicrobial resistance (AMR) rates through a “One Health” approach. The project “Support for the National Plan to Combat Antimicrobial Resistance (SPiNCAR)” was developed to evaluate the level of implementation of actions outlined by the PNCAR, through a self-assessment tool, addressed to regional and local health authorities. This study presents the findings of the first use of the SPiNCAR tool in the Region of Piedmont, detailing the level of implementation as of 31 December 2022. Methods The self-assessment questionnaire is divided into 7 central "areas" representing the main actions against AMR: governance, surveillance and monitoring, appropriate use of antimicrobials, healthcare-associated infection (HAI) control and prevention, education and training, alliance among stakeholders, evaluation of the impact and implementation of the program. Areas are structured into two or more items called "standards", subdivided into "criteria”. Different questionnaires were developed for Regional and Local Authorities. Scores were calculated as the percentage of criteria met within each area, aggregated at both regional and local levels. Results By analysing results at the regional level, it was possible to identify domains of strength in the areas of Governance (79%), Appropriate use of antimicrobials (70%), HAI Control and Prevention (68%) and areas for improvement in Alliance among Stakeholders (18%), Training (33%) and Surveillance (41%). Local authorities showed encouraging median results in Surveillance (37%), Appropriate Use of Antimicrobials (22,5%), and HAI Control and Prevention (21,5%), whereas Implementation (10,5%), Education and Training (8%) and Alliance among Stakeholders (2,5%) need to be improved. Conclusions The first SPiNCAR assessment offered valuable insights to enhance healthcare quality; the evaluation identified stakeholder engagement and training as priority areas for improvement and targeted interventions for AMR containment.